A method for preparing alumina ball carrier by oil column molding process

The synthesis of pseudo-thin alumina pellets through the organic aluminum alcohol method and the inorganic aluminum salt method, combined with the oil column molding process, alumina pellets with high spherical shape, strength and pore volume were prepared, solving the performance of alumina pellets in the prior art. The problem of insufficient is applicable to catalyst support.

CN116212841BActive Publication Date: 2025-01-03FUZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310347427.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-04
Publication Date
2025-01-03
Estimated Expiration
2043-04-04

AI Technical Summary

Technical Problem

In the preparation of alumina sphere carriers, the comprehensive performance of spherical strength, strength and pore volume is insufficient, resulting in performance defects in some catalyst applications, especially poor hydrothermal stability and high impurity content.

Method used

The phthalinated alumina pellets synthesized by the organic aluminum alumina method and the inorganic aluminum salt method are used as raw materials. Alumina pellets are prepared by oil column forming process, combined with acid liquid and gelling agent for gelation treatment, and after aging, washing, drying and Roasted to form alumina spheres with high spherical shape, strength and pore volume.

Benefits of technology

The alumina balls have achieved a comprehensive improvement in the high spherical shape, strength and pore volume, and solved the problem of uneven performance in the prior art. The obtained alumina balls have excellent crushing strength and pore structure, which are suitable as catalysts. Use of vector.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116212841B_ABST
    Figure CN116212841B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing an alumina ball carrier by an oil column forming process, which belongs to the field of catalyst carriers. The method uses two kinds of pseudo-boehmite synthesized by an organic alcohol aluminum method and an inorganic aluminum salt method as raw materials, forms an aluminum sol by peptization, and then mixes with a gelling agent, and then forms an oil column, ages, washes, dries, and roasts to obtain an alumina ball carrier. The alumina ball carrier obtained by the invention has a good pore structure, concentrated pore distribution, uniform pore size, high strength, small bulk density, and regular sphericity, and can be widely used as a catalyst carrier in the fields of petrochemical or fine chemical industry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of catalyst carriers, and in particular relates to a method for preparing an alumina ball carrier by an oil column molding process. Background Art

[0002] Alumina is widely used as a carrier for petrochemical catalysts, such as dehydrogenation catalysts and hydrogenation catalysts, due to its high specific surface area, good adsorption, thermal stability and surface acidity. The commonly used carriers are γAl2O3 or θAl2O3. Industrial catalysts have different shapes and sizes according to different process operation requirements. Therefore, molding operation is the main step in catalyst preparation, which has a great impact on the mechanical strength, activity and life of the catalyst. Some catalysts are easy to break and pulverize due to poor crushing strength, or easy to wear due to poor wear resistance, thus blocking the pipeline and affecting the normal operation. Some catalysts cannot give full play to the catalyst's due effect due to improper shape selection. As far as propane dehydrogenation is concerned, there are two processes, moving bed and fixed bed. For different processes, the carrier of the dehydrogenation catalyst needs to be molded accordingly. For the fixed bed process, the carrier can be a small ball or cylindrical strip with a diameter of 1~2 mm; for the moving bed process, in order to facilitate the cyclic reaction of the catalyst and reduce its mechanical wear, the carrier must be made into a small ball with a diameter of 1~2 mm. At present, the industrial production methods of millimeter-sized alumina pellets include spray drying molding, rolling ball molding, oil column molding, and oil-ammonia column molding. Compared with other methods, the alumina produced by the oil column molding method has good sphericity, smooth surface, and high crushing strength. At present, the oil column molding method has the following routes for preparing alumina pellet carriers;

[0003] (1) Aluminum sol is prepared by mixing aluminum chips or aluminum flakes with hydrochloric acid under high temperature reflux conditions, and then the aluminum oxide ball carrier is obtained by oil column molding;

[0004] (2) Alumina pellet carrier is obtained by preparing aluminum sol from precipitation and peptization of inorganic aluminum salt through oil column molding;

[0005] (3) Aluminum sol is prepared by hydrolysis, condensation and peptization of aluminum alcohol, and then formed into alumina ball carrier by oil column molding;

[0006] The alumina beads prepared by route (1) have poor hydrothermal stability and are therefore not suitable for synthesizing catalyst carriers under harsh reactions. At present, routes (2) and (3) are the most studied. Patent ZL 92109379.9 discloses a method of using inorganic aluminum salt as raw material, preparing aluminum sol after neutralization and peptization treatment, and then preparing aluminum sol by oil column molding, aging, washing, drying, and roasting. Patent CN 87101513A uses aluminum chloride and ammonia water to neutralize aluminum sol, and then prepares aluminum sol by oil-ammonia column molding, aging, and then washing, drying, and steam expansion. The prepared alumina beads have high impurity content, poor strength, and poor sphericity. Patent CN 105502447A discloses a method for preparing alumina pellets by hot oil column molding, wherein the slurry obtained by hydrolyzing aldol, the first gelling agent and water is mixed and then acid-gelled to obtain aluminum sol, and then the second gelling agent is added to form a hot oil column into balls, and then washed, dried and calcined to obtain alumina pellets. However, due to the insufficient performance of a single aluminum sol, it is difficult to prepare alumina pellets with high comprehensive properties (including specific surface area, pore volume, strength, and sphericity), and the obtained alumina pellets often have performance defects in some aspects. Patent CN 111517347A mixes purchased low-sodium pseudo-boehmite powder, macroporous pseudo-boehmite powder and water and stirs them once, then mixes the obtained pseudo-boehmite suspension with acid solution and stirs them twice to obtain aluminum sol, then mixes the aluminum sol with urea and stirs them three times, and then performs oil-ammonia column molding, aging, drying and calcining to obtain alumina pellets with improved performance. However, the two types of pseudo-boehmite used in this method are both synthesized by the inorganic salt method, and the content of various impurities is high. At the same time, the pseudo-boehmite synthesized by the inorganic salt method has poor pore properties. The pores are very easy to be destroyed during the peptization process of spheroidization. Therefore, the pore volume of the obtained alumina spheres is generally low. Summary of the invention

[0007] In view of the above problems, the present invention provides a method for preparing alumina ball carriers by an oil column forming process, which uses two kinds of pseudo-boehmite synthesized by an organic alcohol aluminum method and an inorganic aluminum salt method as raw materials, respectively, and prepares alumina balls by an oil column forming process. The raw materials are widely available, cheap and easy to obtain, the ball preparation process is simple, and will not cause secondary pollution to the environment. The prepared alumina balls not only have good sphericity and high strength, but also have high purity and large pore volume.

[0008] To achieve the above object, the present invention adopts the following technical solution:

[0009] A method for preparing an alumina ball carrier by an oil column molding process comprises the following steps:

[0010] 1) Two types of pseudo-boehmite prepared by organic alcohol aluminum method and inorganic aluminum salt method are mixed with water and stirred evenly to obtain pseudo-boehmite suspension;

[0011] 2) mixing and stirring the obtained pseudo-boehmite suspension and acid solution to obtain aluminum sol;

[0012] 3) The obtained aluminum sol is mixed with a gelling agent and then dripped into a molded oil column at 90-99 °C through a disperser to obtain gel beads. The obtained gel beads are then transferred to an aging kettle, maintained at 120-180 °C for 12-48 h, washed with deionized water until there is no obvious oil stain, and then dried at 100-140 °C for 12-24 h to constant weight, and then calcined at 600-1050 °C for 8-1 h to obtain an alumina bead carrier.

[0013] Furthermore, the organic aluminum alcohol method is to obtain pseudo-boehmite by aging, washing and filtering the slurry prepared by aluminum alcohol through hydrolysis reaction; the aluminum alcohol is one or more of aluminum isopropoxide, aluminum sec-butoxide, aluminum n-pentoxide and aluminum n-hexoxide.

[0014] Furthermore, the inorganic aluminum salt method is to obtain pseudo-boehmite by aging, washing and filtering the slurry prepared by neutralization reaction of inorganic aluminum salt and precipitant; the mass ratio of the inorganic aluminum salt and the precipitant used is 2:1; the inorganic aluminum salt is one or more of aluminum chloride, aluminum nitrate, aluminum sulfate, and aluminum silicate, and the precipitant is one or more of sodium hydroxide, sodium carbonate, sodium aluminate, and ammonia water.

[0015] Furthermore, in step 1), the mass ratio of the pseudo-boehmite prepared by the organic alcohol aluminum method to the pseudo-boehmite prepared by the inorganic aluminum salt method is 1:0.5-10, preferably 1:1-3.

[0016] Furthermore, the mass content of aluminum oxide in the pseudo-boehmite suspension in step 1) is 5% to 30%, preferably 15% to 30%.

[0017] Furthermore, in step 2), the mass ratio of the acid solution to the alumina in the pseudo-boehmite suspension is 0.1-1, and the pH is controlled at 2-5; the acid solution is an aqueous solution of nitric acid, hydrochloric acid, sulfuric acid or formic acid with a mass concentration of 3-30%, preferably a 15-25% nitric acid or hydrochloric acid aqueous solution.

[0018] Furthermore, the stirring in step 2) is carried out at 80-100° C. and the stirring time is 3-7 hours.

[0019] Furthermore, the mass ratio of the gelling agent used in step 3) to the aluminum oxide in the aluminum sol is 0.2-0.6, preferably 0.3-0.5; the gelling agent is one or more of hexamethylenetetramine and urea, preferably hexamethylenetetramine.

[0020] Furthermore, the molding oil used in step 3) is one or more of vacuum pump oil, machine oil, and spindle oil, and its temperature is 90-99° C., preferably vacuum pump oil.

[0021] The beneficial effects of the present invention are:

[0022] The present invention uses pseudo-boehmite synthesized by an inorganic aluminum salt method and pseudo-boehmite synthesized by an organic alcohol aluminum method as raw materials, mixes them with water to obtain a pseudo-boehmite suspension, then mixes the obtained pseudo-boehmite suspension with an acid solution to obtain an aluminum sol, and then mixes the obtained pseudo-boehmite suspension with a gelling agent, forms an aluminum sol through an oil column, ages, washes, dries, and roasts to obtain an alumina ball. In the peptization process, the macropores of the pseudo-boehmite synthesized by the alcohol aluminum method have strong stability and can be completely replicated in the prepared alumina ball; and the pseudo-boehmite synthesized by the inorganic salt method has a good bonding effect after peptization, and can be well compounded with the pseudo-boehmite synthesized by the alcohol aluminum method, so as to facilitate the ball forming process and improve the ball strength. Therefore, the alumina ball prepared by the present invention has the advantages of good pore structure, concentrated pore distribution, uniform and controllable pore size, high crushing strength, small bulk density, regular sphericity, etc., and can solve the problems of non-concentrated pore size distribution and uneven strength distribution existing in the alumina ball carrier prepared by the prior art. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The following are photos of alumina pellets prepared in Examples 1-6 (Serial Nos. 1-6) and Comparative Examples 1-4 (Serial Nos. 7-10). DETAILED DESCRIPTION

[0024] In order to make the contents of the present invention easier to understand, the technical solution of the present invention is further described below in conjunction with specific implementation methods, but the present invention is not limited thereto.

[0025] The crushing strength test of alumina pellet carrier was carried out using DL4 particle strength tester (produced by Dalian Penghui Technology Development Co., Ltd.). A total of 60 samples were measured, and 5 maximum values ​​and 5 minimum values ​​were removed respectively, and then the average value was taken as the crushing strength of alumina pellet carrier. The bulk density is calculated by taking a measuring cylinder, putting a certain mass (M) of alumina pellets, and then tapping and vibrating the alumina pellets to make them pile up evenly. The volume (V) is read through the measuring cylinder, and the bulk density of the alumina pellets is calculated according to the formula ρ=M / V. The measurement was performed 12 times, and 1 maximum value and 1 minimum value were removed respectively. The average value of the rest was taken, which is the bulk density of the alumina pellets.

[0026] Example 1

[0027] Preparation of pseudo-boehmite: 375 g of aluminum nitrate was dissolved in 350 g of 12% ammonia solution, stirred at a constant speed for 3 h at 60 °C to allow the two to react fully, then raised to 70 °C and allowed to stand for 2 h to allow the product to be fully induced to transform, and the product was washed and filtered to obtain pseudo-boehmite synthesized by the aluminum salt method; 102 g of aluminum isopropoxide was dissolved in a mixed solution of 162 g of water and 58 g of isopropanol, stirred at a constant speed for 3 h at 60 °C to allow the two to react fully, then raised to 70 °C and allowed to stand for 2 h to allow the product to be fully induced to transform, and the product was washed and filtered to obtain pseudo-boehmite synthesized by the alcohol aluminum method.

[0028] Preparation of aluminum sol: Take 100 g of pseudo-boehmite synthesized by the aluminum salt method and 50 g of pseudo-boehmite synthesized by the alcohol aluminum method, add 300 g of deionized water and stir continuously at 80 °C to obtain a pseudo-boehmite suspension with an aluminum oxide mass content of 20%; then add 12 g of 10% mass concentration nitric acid solution and stir at 100 °C for 5 hours to obtain aluminum sol (pH 2~5).

[0029] Aluminum sol molding: Add 72 g of hexamethylenetetramine to 400 g of aluminum sol, stir thoroughly and then use a No. 18 dispersed dripper to drip into 90°C vacuum pump oil for molding (the oil column height is 5 meters). Separate the molded gel balls from the oil and age them in an aging kettle at 150°C for 12 hours.

[0030] Preparation of alumina beads: The aged sol beads were washed with deionized water until no obvious oil stains were left, then dried at 130°C for 12 hours to constant weight, and then calcined at 1050°C for 12 hours to obtain alumina beads with a θ phase crystal form.

[0031] Example 2

[0032] Preparation of pseudo-boehmite: 375 g of aluminum nitrate was dissolved in 350 g of 8% ammonia solution, stirred at 60 °C for 3 h to allow the two to react fully, then raised to 70 °C and allowed to stand for 2 h to allow the product to be fully induced to transform, and the product was washed and filtered to obtain pseudo-boehmite synthesized by the aluminum salt method; 240 g of aluminum sec-butoxide was dissolved in a mixed solution of 195 g of water and 105 g of sec-butanol, stirred at 60 °C for 3 h to allow the two to react fully, then raised to 70 °C and allowed to stand for 2 h to allow the product to be fully induced to transform, and the product was washed and filtered to obtain pseudo-boehmite synthesized by the alcohol aluminum method.

[0033] Preparation of aluminum sol: Take 100 g of pseudo-boehmite synthesized by the aluminum salt method and 50 g of pseudo-boehmite synthesized by the alcohol aluminum method, add 350 g of deionized water and stir continuously at 80 °C to obtain a pseudo-boehmite suspension with an aluminum oxide mass content of 20%; then add 15 g of 10% mass concentration nitric acid solution and stir at 100 °C for 5 hours to obtain aluminum sol (pH 2~5).

[0034] Aluminum sol molding: Add 85 g of hexamethylenetetramine to 400 g of aluminum sol, stir thoroughly and then use a No. 19 disperser to drip into 95°C vacuum pump oil for molding (the oil column height is 5 meters). Separate the molded gel balls from the oil and age them in an aging kettle at 160°C for 12 hours.

[0035] Preparation of alumina beads: The aged sol beads were washed with deionized water until no obvious oil stains were left, then dried at 130°C for 8 hours to constant weight, and then calcined at 1050°C for 12 hours to obtain alumina beads with a θ phase crystal form.

[0036] Example 3

[0037] Preparation of pseudo-boehmite: 343 g of aluminum sulfate and 164 g of sodium aluminate were dissolved in 500 g of deionized water in turn, stirred at a constant speed for 3 h at 70 °C to allow the two to react fully, then raised to 80 °C and allowed to stand for 2 h to allow the product to be fully induced to transform, and the product was washed and filtered to obtain pseudo-boehmite synthesized by the aluminum salt method; 204 g of aluminum isopropoxide was dissolved in a mixed solution of 324 g of water and 106 g of isopropanol, stirred at a constant speed for 3 h at 70 °C to allow the two to react fully, then raised to 80 °C and allowed to stand for 2 h to allow the product to be fully induced to transform, and the product was washed and filtered to obtain pseudo-boehmite synthesized by the alcohol aluminum method.

[0038] Preparation of aluminum sol: Take 100 g of pseudo-boehmite synthesized by aluminum salt method and 100 g of pseudo-boehmite synthesized by aluminum alcohol method, add 466 g of deionized water and stir continuously at 80 °C to obtain a pseudo-boehmite suspension with an aluminum oxide mass content of 18%; then add 12 g of 12% mass concentration nitric acid solution and stir at 100 °C for 5 hours to obtain aluminum sol (pH 2~5).

[0039] Aluminum sol molding: Add 135g of hexamethylenetetramine to 500g of aluminum sol, stir and mix thoroughly, then use a No. 18 disperser to drip into 100°C vacuum pump oil for molding (the oil column height is 5 meters). Separate the molded gel balls from the oil and age them in an aging kettle at 160°C for 12 hours.

[0040] Preparation of alumina beads: The aged sol beads were washed with deionized water until no obvious oil stains were left, then dried at 120°C for 12 hours to constant weight, and then calcined at 1050°C for 12 hours to obtain alumina beads with a θ phase crystal form.

[0041] Example 4

[0042] Preparation of pseudo-boehmite: 343 g of aluminum sulfate and 164 g of sodium aluminate were dissolved in 500 g of water, stirred at 70 °C for 3 h to allow the two to react fully, then raised to 80 °C and allowed to stand for 2 h to allow the product to be fully induced to transform, and the product was washed and filtered to obtain pseudo-boehmite synthesized by the aluminum salt method; 265 g of aluminum sec-butoxide was dissolved in a mixed solution of 342 g of water and 150 g of sec-butanol, stirred at 70 °C for 3 h to allow the two to react fully, then raised to 80 °C and allowed to stand for 2 h to allow the product to be fully induced to transform, and the product was washed and filtered to obtain pseudo-boehmite synthesized by the alcohol aluminum method.

[0043] Preparation of aluminum sol: Take 100 g of pseudo-boehmite synthesized by the aluminum salt method and 90 g of pseudo-boehmite synthesized by the alcohol aluminum method, add 500 g of deionized water and stir continuously at 80 °C to obtain a pseudo-boehmite suspension with an aluminum oxide mass content of 18%; then add 15 g of 10% mass concentration nitric acid solution and stir at 100 °C for 5 hours to obtain aluminum sol (pH 2~5).

[0044] Aluminum sol molding: Add 100 g of hexamethylenetetramine to 450 g of aluminum sol, stir and mix thoroughly, then use a No. 19 disperser to drip into 95°C vacuum pump oil for molding (the oil column height is 5 meters). Separate the molded gel balls from the oil and age them in an aging kettle at 160°C for 12 hours.

[0045] Preparation of alumina beads: The aged sol beads were washed with deionized water until no obvious oil stains were left, then dried at 120°C for 12 hours to constant weight, and then calcined at 1050°C for 12 hours to obtain alumina beads with a θ phase crystal form.

[0046] Example 5

[0047] Preparation of pseudo-boehmite: 162 g of aluminum silicate and 212 g of sodium carbonate were dissolved in 400 g of water, stirred at 80 °C for 2 h to allow the two to react fully, then raised to 90 °C and allowed to stand for 2 h to allow the product to be fully induced to transform, and the product was washed and filtered to obtain pseudo-boehmite synthesized by the aluminum salt method; 204 g of aluminum isopropoxide was dissolved in a mixed solution of 324 g of water and 116 g of isopropanol, stirred at 80 °C for 2 h to allow the two to react fully, then raised to 90 °C and allowed to stand for 2 h to allow the product to be fully induced to transform, and the product was washed and filtered to obtain pseudo-boehmite synthesized by the alcohol aluminum method.

[0048] Preparation of aluminum sol: Take 150g of pseudo-boehmite synthesized by the aluminum salt method and 100g of pseudo-boehmite synthesized by the alcohol aluminum method, add 470g of deionized water and stir continuously at 90°C to obtain a pseudo-boehmite suspension with an aluminum oxide mass content of 21%; then add 12g of 15% mass concentration nitric acid solution and stir at 100°C for 5 hours to obtain aluminum sol (pH 2~5).

[0049] Aluminum sol molding: Add 100 g of hexamethylenetetramine to 470 g of aluminum sol, stir and mix thoroughly, then use a No. 18 disperser to drip into 100 °C vacuum pump oil for molding (the oil column height is 5 meters). Separate the molded gel balls from the oil and age them in an oven at 150 °C for 12 hours.

[0050] Preparation of alumina beads: The aged sol beads were washed with deionized water until no obvious oil stains were left, then dried at 110°C for 12 hours to constant weight, and then calcined at 1050°C for 12 hours to obtain alumina beads with a θ phase crystal form.

[0051] Example 6

[0052] Preparation of pseudo-boehmite: 162 g of aluminum silicate and 212 g of sodium carbonate were dissolved in 400 g of water, stirred at 80 °C for 2 h to allow the two to react fully, then raised to 90 °C and allowed to stand for 2 h to allow the product to be fully induced to transform, and the product was washed and filtered to obtain pseudo-boehmite synthesized by the aluminum salt method; 165 g of aluminum sec-butoxide was dissolved in a mixed solution of 242 g of water and 100 g of sec-butanol, stirred at 80 °C for 2 h to allow the two to react fully, then raised to 90 °C and allowed to stand for 2 h to allow the product to be fully induced to transform, and the product was washed and filtered to obtain pseudo-boehmite synthesized by the alcohol aluminum method.

[0053] Preparation of aluminum sol: Take 150 g of pseudo-boehmite synthesized by the aluminum salt method and 100 g of pseudo-boehmite synthesized by the alcohol aluminum method, add 520 g of deionized water and stir continuously at 90 °C to obtain a pseudo-boehmite suspension with an aluminum oxide mass content of 21%; then add 14 g of 10% mass concentration nitric acid solution and stir at 100 °C for 5 hours to obtain aluminum sol (pH 2~5).

[0054] Aluminum sol molding: Add 105 g of hexamethylenetetramine to 580 g of aluminum sol, stir thoroughly and then use a No. 19 disperser to drip into 100 °C vacuum pump oil for molding (the oil column height is 5 meters). Separate the molded gel balls from the oil and age them in an aging kettle at 150 °C for 12 hours.

[0055] Preparation of alumina beads: The aged sol beads were washed with deionized water until no obvious oil stains were left, then dried at 110°C for 12 hours to constant weight, and then calcined at 1050°C for 12 hours to obtain alumina beads with a θ phase crystal form.

[0056] Comparative Example 1

[0057] Preparation of pseudo-boehmite: 375 g of aluminum nitrate was dissolved in 350 g of 8% ammonia solution, stirred at 60 °C for 2 h to allow the two to react fully, then raised to 70 °C and allowed to stand for 2 h to allow the product to be fully induced to transform, and the product was washed and filtered to obtain pseudo-boehmite synthesized by the aluminum salt method;

[0058] Preparation of aluminum sol: Take 100 g of pseudo-boehmite synthesized by the inorganic aluminum salt method, add 200 g of deionized water and stir continuously at 80 °C to obtain a pseudo-boehmite suspension with an aluminum oxide mass content of 20%; then add 20 g of 10% mass concentration nitric acid solution and stir at 100 °C for 5 hours to obtain aluminum sol (pH 2~5).

[0059] Aluminum sol molding: Add 75 g of hexamethylenetetramine to 250 g of aluminum sol, stir and mix thoroughly, then use a No. 19 disperser to drip into 95°C vacuum pump oil for molding (the oil column height is 5 meters). Separate the molded gel balls from the oil and age them in an aging kettle at 160°C for 12 hours.

[0060] Preparation of alumina beads: The aged sol beads were washed with deionized water until no obvious oil stains were left, then dried at 130°C for 8 hours to constant weight, and then calcined at 1050°C for 12 hours to obtain alumina beads with a θ phase crystal form.

[0061] Comparative Example 2

[0062] Preparation of pseudo-boehmite: 204 g of aluminum sec-butoxide was dissolved in a mixed solution of 344 g of water and 116 g of sec-butanol, and stirred at 70 °C for 2 h to allow the two to react fully. The temperature was then raised to 80 °C and allowed to stand for 2 h to allow the product to be fully induced to transform. The product was washed and filtered in turn to obtain pseudo-boehmite synthesized by the aluminum alcohol method.

[0063] Preparation of aluminum sol: Take 100 g of pseudo-boehmite synthesized by the alcohol aluminum method, add 200 g of deionized water and stir continuously at 80 °C to obtain a pseudo-boehmite suspension with an aluminum oxide content of 20%; then add 20 g of 10% nitric acid solution and stir at 100 °C for 5 hours to obtain an aluminum sol (pH 2~5).

[0064] Aluminum sol molding: Add 72 g of hexamethylenetetramine to 250 g of aluminum sol, stir and mix thoroughly, then use a No. 19 disperser to drip into 95°C vacuum pump oil for molding (the oil column height is 5 meters). Separate the molded gel balls from the oil and age them in an aging kettle at 160°C for 12 hours.

[0065] Preparation of alumina beads: The aged sol beads were washed with deionized water until no obvious oil stains were left, then dried at 130°C for 8 hours to constant weight, and then calcined at 1050°C for 12 hours to obtain alumina beads with a θ phase crystal form.

[0066] Comparative Example 3

[0067] Preparation of aluminum sol: Take 50 g of pseudo-boehmite and 50 g of macroporous pseudo-boehmite prepared by the aluminum salt method, add them into a beaker filled with 180 g of deionized water, stir at room temperature for 1 hour to form a uniform suspension with an aluminum oxide mass content of 20%, then add 15 g of 10% mass concentration nitric acid solution, and stir at 100 °C for 5 hours to obtain aluminum sol.

[0068] Aluminum sol molding: Add 20 g of hexamethylenetetramine to the above aluminum sol, stir and mix thoroughly, then use a No. 19 disperser to drip into 100°C vacuum pump oil for molding (the oil column height is 5 meters). Separate the molded gel balls from the oil and age them in an aging kettle at 150°C for 12 hours.

[0069] Preparation of alumina beads: The aged sol beads were washed with deionized water until no obvious oil stains were left, then dried at 130°C for 12 hours to constant weight, and then calcined at 1050°C for 12 hours to obtain alumina beads with a θ phase crystal form.

[0070] Comparative Example 4

[0071] Preparation of pseudo-boehmite: 204 g of aluminum isopropoxide and aluminum sec-butoxide were dissolved in a mixed solution of 344 g of water and 116 g of isopropanol or sec-butanol, respectively, and stirred at a constant speed for 2 h at 70 °C to allow the two to react fully, then raised to 80 °C and allowed to stand for 2 h to allow the product to be fully induced to transform. The products were washed and filtered in turn to obtain two types of pseudo-boehmite synthesized from aluminum isopropoxide and aluminum sec-butoxide, respectively.

[0072] Preparation of aluminum sol: Take 50g of each of two pseudo-boehmite prepared by aluminum isopropoxide and aluminum sec-butoxide, add them into a beaker filled with 180g of deionized water, stir at room temperature for 1 hour to form a uniform suspension with an aluminum oxide mass content of 20%, then add 17g of 10% nitric acid solution, and stir at 100℃ for 5 hours to obtain aluminum sol.

[0073] Aluminum sol molding: Add 20 g of hexamethylenetetramine to the above aluminum sol, stir and mix thoroughly, then use a No. 19 disperser to drip into 100°C vacuum pump oil for molding (the oil column height is 5 meters). Separate the molded gel balls from the oil and age them in an aging kettle at 150°C for 12 hours.

[0074] Preparation of alumina beads: The aged sol beads were washed with deionized water until no obvious oil stains were left, then dried at 130°C for 12 hours to constant weight, and then calcined at 1050°C for 12 hours to obtain alumina beads with a θ phase crystal form.

[0075] Table 1 shows the performance test results of the alumina balls obtained in the examples and comparative examples.

[0076] Table 1

[0077]

[0078] It can be seen from Table 1 that the strength of the samples of the embodiment obtained by using the two pseudo-boehmite synthesized by the organic alcohol aluminum method and the inorganic salt method as raw materials is greater than 50N, the pore volume is more than 0.75 ml / g, and the bulk density is less than 0.65 g / cm 3, which can meet the needs of dehydrogenation catalyst carriers. Comparative Example 1 uses pseudo-boehmite prepared by inorganic salt method as raw material to synthesize alumina beads. Although it has high strength, it has small pore volume and high bulk density. Comparative Example 2 uses pseudo-boehmite prepared by alcohol aluminum method as raw material to synthesize alumina beads. Although it has large pore volume and small bulk density, its strength is low. Comparative Example 3 uses two kinds of pseudo-boehmite prepared by inorganic salt method as raw material to synthesize alumina beads. Although it has high strength, its pore volume is general and its bulk density is high. Comparative Example 4 uses two kinds of pseudo-boehmite prepared by alcohol aluminum method as raw material to synthesize alumina beads. Although it has large pore volume and small bulk density, its strength is low. The above comparison proves that alumina beads with high strength, large pore volume and low bulk density can be prepared using two kinds of pseudo-boehmite synthesized by alcohol aluminum method and inorganic salt method as raw materials.

[0079] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.

Claims

1. A method for preparing alumina ball carrier by oil column molding process, characterized in that: The steps include: 1) Two types of pseudo-boehmite prepared by organic alcohol aluminum method and inorganic aluminum salt method are mixed with water and stirred evenly to obtain pseudo-boehmite suspension; 2) mixing and stirring the obtained pseudo-boehmite suspension and acid solution to obtain aluminum sol; 3) mixing the obtained aluminum sol with a gelling agent and dripping it into a molding oil column for molding, and then aging, washing, drying and calcining to obtain the alumina ball carrier; The mass ratio of the pseudo-boehmite prepared by the organic alcohol aluminum method to the pseudo-boehmite prepared by the inorganic aluminum salt method used in step 1) is 1:0.5-10.

2. The method for preparing alumina ball carrier by oil column forming process according to claim 1, characterized in that: Step 1) The mass content of aluminum oxide in the pseudo-boehmite suspension is 5-30%.

3. The method for preparing alumina ball carrier by oil column forming process according to claim 1, characterized in that: The mass ratio of the acid solution used in step 2) to the alumina in the pseudo-boehmite suspension is 0.1-1, and the pH is controlled at 2-5; the acid solution is an aqueous solution of nitric acid, hydrochloric acid, sulfuric acid or formic acid with a mass concentration of 3-30%.

4. The method for preparing alumina ball carrier by oil column forming process according to claim 1, characterized in that: The stirring in step 2) is carried out at 80-100°C for 3-7 hours.

5. The method for preparing alumina ball carrier by oil column forming process according to claim 1, characterized in that: The mass ratio of the gelling agent used in step 3) to the aluminum oxide in the aluminum sol is 0.2-0.6; the gelling agent is one or more of hexamethylenetetramine and urea.

6. The method for preparing alumina ball carrier by oil column forming process according to claim 1, characterized in that: The molding oil used in step 3) is one or more of vacuum pump oil, machine oil, and spindle oil, and its temperature is 90~99°C.

7. The method for preparing alumina ball carrier by oil column forming process according to claim 1, characterized in that: The aging temperature in step 3) is 120-180°C and the aging time is 12-48 hours.

8. The method for preparing alumina ball carrier by oil column forming process according to claim 1, characterized in that: The drying temperature in step 3) is 100-140°C and the drying time is 12-24 hours.

9. The method for preparing alumina ball carrier by oil column forming process according to claim 1, characterized in that: The calcination temperature in step 3) is 600-1050°C and the calcination time is 8-12h.